2014
DOI: 10.1103/physrevc.90.054308
|View full text |Cite
|
Sign up to set email alerts
|

O16+O16molecular structures of positive- and negative-parity superdeformed bands in

Abstract: The structures of excited states in 34 S are investigated using the antisymmetrized molecular dynamics and generator coordinate method (GCM). The GCM basis wave functions are calculated via energy variation with a constraint on the quadrupole deformation parameter β. By applying the GCM after parity and angular momentum projections, the coexistence of two positive-and one negative-parity superdeformed (SD) bands are predicted, and low-lying states and other deformed bands are obtained. The SD bands have struct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Note that the SD configurations, which have the structure of 16 O+ 16 O+two valence neutrons in molecular orbitals, have recently been predicted in the AMD+GCM calculations of Ref. [7].…”
Section: Clusterization and Molecular Structuresmentioning
confidence: 82%
See 3 more Smart Citations
“…Note that the SD configurations, which have the structure of 16 O+ 16 O+two valence neutrons in molecular orbitals, have recently been predicted in the AMD+GCM calculations of Ref. [7].…”
Section: Clusterization and Molecular Structuresmentioning
confidence: 82%
“…There is a considerable interest to the study of cluster structures and extremely deformed shapes in light nuclei [1][2][3][4][5][6][7][8][9][10]. Many of these structures are described in terms of clusters, the simplest one being the α-particle [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coexistence of positive-and negative-parity SD bands and their structures are discussed, focusing on 16 O + 16 O + valence neutrons in molecular orbitals around the two 16 O cores. Details of this study are reported in [13].…”
Section: Introductionmentioning
confidence: 99%